2007
DOI: 10.1089/vbz.2006.0602
|View full text |Cite
|
Sign up to set email alerts
|

Host Choice and West Nile Virus Infection Rates in Blood-Fed Mosquitoes, Including Members of theCulex pipiensComplex, from Memphis and Shelby County, Tennessee, 2002–2003

Abstract: The source of bloodmeals in 2,082 blood-fed mosquitoes collected from February 2002 through December 2003 in Memphis and surrounding areas of Shelby County, Tennessee were determined. Members of the genus Culex and Anopheles quadrimaculatus predominated in the collections. Members of the Cx. pipiens complex and Cx. restuans were found to feed predominately upon avian hosts, though mammalian hosts made up a substantial proportion of the bloodmeals in these species. No significant difference was seen in the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 47 publications
7
128
0
2
Order By: Relevance
“…pipiens complex and to characterize populations and zones of hybridization (Bourguet et al 1998, Aspen & Savage 2003, Smith & Fonseca 2004, Savage et al 2007, Sanogo et al 2008, Kothera et al 2009). The fragment of the ace-2 locus was amplified from each DNA sample by PCR in a final reaction volume of 50 μL with 2 mM Mg ++ , 20 mM Tris-HCl (pH 8.4), 50 mM KCl, 0.5 mM of each primer, 0.2 mM dNTP mix, 2 U of Taq DNA polymerase (Invitrogen) and approximately 6.0 ng of genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…pipiens complex and to characterize populations and zones of hybridization (Bourguet et al 1998, Aspen & Savage 2003, Smith & Fonseca 2004, Savage et al 2007, Sanogo et al 2008, Kothera et al 2009). The fragment of the ace-2 locus was amplified from each DNA sample by PCR in a final reaction volume of 50 μL with 2 mM Mg ++ , 20 mM Tris-HCl (pH 8.4), 50 mM KCl, 0.5 mM of each primer, 0.2 mM dNTP mix, 2 U of Taq DNA polymerase (Invitrogen) and approximately 6.0 ng of genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…In a study in Tucson, USA, blood meal analysis revealed that 50% of Cx. quinquefasciatus females fed on humans and 32% on birds, respectively (and therefore this species is considered to be a potential West Nile virus vector; Zinser et al 2004), whereas in Tenessee, USA, and Mexico they were found to feed less on humans than on birds (Eilizondo-Quiroga et al 2006, Savage et al 2007. In addition, a greater percentage of Cx.…”
Section: Van Der Goes Van Naters and Carlson 2006)mentioning
confidence: 99%
“…[31][32][33][34] In St. Tammany Parish during the 2002 outbreak, Cx. quinquefasciatus was the primary enzootic/epidemic vector, with Cx.…”
Section: Ecology Of West Nile Virus Vectors In Louisianamentioning
confidence: 99%
“…54 Culex erraticus feeds predominantly on mammals, but will also feed on birds. 32,49 Studies conducted in Tennessee showed that avian blood meal hosts of Cx. erraticus included American robins (Turdus migratorius), common grackles (Quiscalus quiscula), house finches (Carpodacus mexicanus), and Carolina wrens (Thryothorus ludovicianus).…”
Section: Ecology Of West Nile Virus Vectors In Louisianamentioning
confidence: 99%
See 1 more Smart Citation